In vitro Topical Delivery of Non-Steroidal Anti-inflammatory Drugs through Human Skin - Vincent, Claire-Marie; Laugel, Cécile; Marty, Jean-Paul (Arzneimittelforschung, 1999)
The objective of the present study was to evaluate in vitro the percutaneous absorption, across human skin. of 5 non-steroidal anti-inflammatory drugs (NSAIDs) formulated as gels: ketoprofen (CAS 22071-15-4), epolamine diclofenac (CAS 15307-86-5), piroxicam (CAS 36322-90-4) and niflumic acid (CAS 4394-00-7) or as emulgel: diclofenac sodium (CAS 15307-79-6) and ‘to compare the different formulations as drug delivery systems. Because the concentrations of the NSAIDs in the different excipients were not identical, the comparison of their diffusional properties was expressed in term of release efficiency (or diffusion efficacy). The results obtained show that, across human skin under standardized experimental conditions, ketoprofen and piroxicam have the best rank order followed by niflumic acid. diclofenac sodium and epolamine diclofenac.
Keywords: Anti-inflammatories, in vitro percutaneous diffusion, non-steroidal; Diclofenac sodium; Epolamine diclofenac; Ketoprofen; Niflumic acid; Piroxicam; Topical NSAIDs